Peningkatan Kapasitas Pemahaman Bantuan Hidup Dasar dan Penanganan Bencana Kebakaran Komunitas Sentra Komunikasi Mitra Polri Kapanewon Kasihan - Deby Zulkarnain Rahadian Syah; Brigita Nandatul Octalila; Ferra Fadhulil Jannah (The Journal of Innovation in Community Empowerment, 2023)
Disaster in terms is an event that threatens and disrupts human life and livelihood. The causes can be natural factors, as well as non-natural ones, it can also be humans themselves, causing fatalities, environmental damage, loss of property, and psychological factors. Disaster emergency response is an activity that is carried out immediately when a disaster occurs to deal with the negative impacts, such as transporting victims, fulfilling basic needs or basic life assistance, and rescue. Nurses are health professionals who have basic skills in Emergency Management Training or often called PPGD. Nurses in providing primary nursing care are providing health promotion to the community. This is in line with the condition of the community that requires an understanding of how to handle victims in a disaster, especially fires. The results of the service are published in a scientific journal of community service at Jenderal Achmad Yani University, Yogyakarta.